PENDIDIKAN ISLAM DALAM MENINGKATKAN SINERGI ANTAR MASYARAKAT NELAYAN - Hafid (P3M STAI MIFTAHUL ULUM LUMAJANG, 2023)
Islamic education is one of the important pillars in community development. Islamiceducation can play a role in increasing synergy between fishing communities. This is becauseIslamic education teaches the values of togetherness, mutual assistance and mutualcooperation. These values can become the basis for fishing communities to work togetherto improve their welfare. This type of research is classified as qualitative with the researchapproach used being a normative and sociological approach, namely environmentalinteractions in accordance with social units, individuals, groups, institutions or society. Thedata source for this research is the fishing community. Furthermore, the data collectionmethods used were observation, interviews and documentation. Then data processing andanalysis techniques are carried out through three stages, namely: data reduction, datapresentation, and drawing conclusions. The results of the research concluded that IslamicEducation, Syirkah Cooperation Agreements were divided into two types, namely syirkahamlak and syirkah uqud. Where syirkah amlak is divided into two forms, namely syirkahamlak ikhtiyar and syirkah amlak ijbar. Meanwhile, regarding the division of uqud syirkah,scholars differ in their form. However, according to But, several jurists have differentopinions in dividing the various types of al-Uqud syirkah, namely: according to Hanabilah thissyirkah is divided into five, including; Syirkah 'Inan, Syirkah Mufawadhah, Syirkah Abdan,Syirkah Wujuh, Syirkah Mudharabah. Meanwhile, according to Hanafiyah, this syirkah isdivided into six, namely; Syirkah Amwal, Syirkah A'mal, Syirkah Wujuh, each of these threeforms is divided into mufawadhah and 'inan. According to Malikiyah and Syafi'iyah, thissyirkah is divided into four, including; Syirkah 'Inan, Syirkah Mufawadhah, Syirkah Abdan,Syirkah Wujuh. Shirkah if it has fulfilled the pillars of syirkah, namely the presence of partiesand consent.